Pengembangan Buku Program Vokasi Musik (M-VET) yang Adaptif untuk Pembelajaran dengan Siswa dengan Hambatan Penglihatan - Teofilus Seisoria, Manggalagita; Ediyanto, Ediyanto; Safiul Ummah, Umi; Romadlon Junaidi, Ahsan; Samawi, Ahmad (Green Publisher Indonesia, 2025)
This research aims to develop an adaptive music vocational program book as a guidebook for prospective music vocational teachers for visually impaired students. This book is designed in the context of facilitating prospective music teachers in delivering learning materials that are in accordance with the needs of visually impaired students in the field of music. The process of developing this book uses Research and Development (R&D) research methods with the Sustainable Instrument Development model consisting of Information Gathering, Planning, Establishing The Initial Product and Validating. At each stage, revisions are carried out in accordance with the newness of relevant knowledge. The development of the book is adjusted to the guidelines for becoming a level III music teacher to be more specific to visually impaired students with strategies and alternatives to learning music, such as the use of braille music notation, audio materials and learning material ideas that can help prospective music vocational teachers in learning music knowledge and skills for visually impaired students. The results of the study show that the developed books are relevant to the needs of visually impaired students and can be developed to improve the quality of individual music teachers in schools with a musical perspective in a special education environment. In addition, this book is also expected to be implemented and refined in terms of competency and accessibility units so that it can enrich the design of teaching methods that are more specific to the needs of visually impaired students.